GDT312 : Studio project II / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2017)
A comprehensive graphic design course which allows students to pursue their main area of interest in graphic design specialized areas. This course will equip students with a greater understanding and appreciation of contemporary graphic design realm. In this advance design practice course, the student is guided to find a new way in their creations look without ignoring the basic principles. There are 4 (four) sets of comprehensive assignment to be covered: 1) Brand Identity Design/ Corporate Identity Design a) Identity Design b) Type Design & Lettering c) Packaging Design 2) Advertising a) Advertising Design & Art Direction b) Promotional Design c) Supporting Marketing Tools 3) Illustration a) Graphic Illustration 2D/ 3D b) Manual Illustration c) Publication Design 4) Multimedia a) Web Interface Design